Interdisciplinary thinking: its theoretical foundations and its impact on modern linguistic lesson - hedda, hasna (The Notebooks of the Algerian Poetics Laboratory Journal, 2025)
The subject of this article Is the duality of Interdisciplinary and disciplinary and their knowledge production and the Importance of each one In developing science and deepening research in various fields and morritoring the relationship between them on on the basis of independence, which is the occlusion of the self and the subject, or the openess that contributes and ensures continuity, renewal and development and it has become clear that interdisciplinary studies do not mean the abolition of disciplinary but an alternative strategy to solve problems and answer various questions that Can no longer be answered by disciplinary . Therefore, we sought In this research paper to: Define the term Interdisciplinary and the term disciplinary, clarifying the difference between them, highlighting the Importance of Interdisciplinary studies at the cognitive level and the obstacles facing interdisciplinary studies to expand knowledge and talking about the role of interdisciplinary studiesin developing the modern linguistics lesson, then presenting the most prominent Arab opinions about Interdisciplinary studies and their fields.